Evaluation of the Readiness of Islamic Religious Education Teachers in the Implementation of the Independent Learning Curriculum - Mufti, Alex Yusron Al; Agustiana, Sylvia Putri; Ali, Zuraimy; Gunawan, Muhammad Ali (Newinera Publisher, 2025)
This study investigates the readiness of Islamic Education (PAI) teachers at MA Mathalibul Huda Mlonggo in implementing the Merdeka Belajar Curriculum, which emphasizes flexibility, student-centered learning, and the development of the Pancasila Student Profile. Using qualitative methods through interviews with teachers, school leaders, and curriculum coordinators, the research reveals that PAI teachers have shown commendable enthusiasm and conceptual understanding of the curriculum. They have participated in workshops, socialization programs, and independent training; however, practical application remains limited, particularly in preparing teaching modules, assessment planning, and the integration of differentiated instruction. Institutional efforts, including training and collaboration with educational stakeholders, have strengthened this transition. Nevertheless, challenges persist in digital readiness, curriculum design skills, and comprehensive pedagogical adaptation. Overall, the findings highlight that successful implementation of the Merdeka Curriculum requires continuous professional development, managerial support, and technological integration to align educational practices with national transformation goals in fostering competent, character-driven, and culturally grounded learners.